2010
DOI: 10.1007/s00382-010-0785-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate modelling of the 2006 West African monsoon: sensitivity to convection and planetary boundary layer parameterisation using WRF

Abstract: International audienceRegional climate model (RCM) is a valuable scientific tool to address the mechanisms of regional atmospheric systems such as the West African monsoon (WAM). This study aims to improve our understanding of the impact of some physical schemes of RCM on the WAM representation. The weather research and forecasting model has been used by performing six simulations of the 2006 summer WAM season. These simulations use all combinations of three convective parameterization schemes (CPSs) and two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
101
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 59 publications
12
101
2
Order By: Relevance
“…This is consistent with the findings of Flaounas et al (2011), who showed drastic changes depending on the physical parameterizations.…”
Section: Illustration With the 2009 Season: Wavelet Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the findings of Flaounas et al (2011), who showed drastic changes depending on the physical parameterizations.…”
Section: Illustration With the 2009 Season: Wavelet Analysissupporting
confidence: 92%
“…Crétat et al (2015) conducted a more detailed analysis on the relationship between AEWs and daily rainfall, using various regional simulations, and revealed the fairly good performance of RCM in terms of spatial and temporal phases. Although a set of arguments tends to confirm the real added value of RCMs, Flaounas et al (2011) have shown a decisive impact of physical parameterizations on the monsoon onset and precipitation intraseasonal variability, implying that substantial work is still needed to calibrate or to adapt RCMs for Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Using MM5, Solman and Pessacg (2012) found that based on model performance in sea level pressure, surface temperature, and precipitation simulation from October through November, no single combination was found to perform the best over the entire domain and during their entire integration period for their La Plata Basin study. Flaounas et al (2011) found that the PBLs seem to have the strongest effect on the vertical distributions of temperature and humidity, and rainfall amount, and convective schemes strongly influence precipitation variability in their WRF/ARW simulations for the year 2006 West African Monsoon simulation.…”
Section: Physical Processes I: Convective Precipitation Processesmentioning
confidence: 98%
“…Over South Africa, Ratna et al (2013) indicated that in WRF/ARW, the BMJ scheme seemed to reproduce the intensity of rainfall anomalies and also exhibited the highest correlation with observed interannual summer rainfall variability there compared with other schemes. Due to the development of the new general mesoscale forecast models, such as WRF, which consist of broad selections of different physical parameterizations, studies have combined different cumulus schemes, radiation schemes, and planetary boundary layer (PBL) schemes in an attempt to define the optimal combination of physical parameterizations for certain regional climate studies (e.g., Xu and Small, 2002;Leung et al, 2003b;Lynn et al, 2010;Flaounas et al, 2011;Solman and Pessacg, 2012;Yuan et al, 2012). Using MM5, Solman and Pessacg (2012) found that based on model performance in sea level pressure, surface temperature, and precipitation simulation from October through November, no single combination was found to perform the best over the entire domain and during their entire integration period for their La Plata Basin study.…”
Section: Physical Processes I: Convective Precipitation Processesmentioning
confidence: 99%
“…For example, studies on the impact of soil moisture on regional climate (Kim and Hong 2007;Sato and Xue 2013;Liu et al 2014) hardly consider the different model performance between physical schemes combinations. Although the new general meso-scale forecast models (such as Weather Research and Forecasting (WRF) model) were developed to consist of broad selections of physical parameterizations, sensitivity studies were mainly conducted for different model settings and physical processes, respectively (Flaounas et al 2011;Waliser et al 2011;Yang et al 2012;Ratna et al 2014).…”
Section: Introductionmentioning
confidence: 99%